Storymaking: an investigation on the process of co-created brand storytelling in the sporting goods industry - Langaro, D. (2021)
Brand storymaking is the new, evolving buzzword in marketing and branding practice. The current study explores the evolving concept of brand storymaking as a highly relevant future branding and communications tool for the sporting goods industry (SGI). In response to increasing consumer involvement, the term of brand storymaking refers to brand storytelling in the context of co-creation. In recent years, brand storytelling has become an important content creative strategy in communications (Woodside, 2010; Lundqvist et al., 2013; Singh & Sonnenburg, 2012), with brands being promoted by means of stories which are created and distributed by marketers, in a one-to-many traditional approach (e.g. advertising campaigns).